Clean Routes to Sustainable Polymers - Lentz, J. C. (2024)
The first experimental chapter of this thesis, Chapter 2, reports on the use of Novozym 435 as a catalyst for the synthesis of acrylamide initiated aliphatic polyesters by enzymatic ring-opening polymerisation. N-Hydroxyethyl acrylamide was utilised as a functional initiator to overcome transesterification issues associated with the use of acrylates in combination with Novozym 435. Two lactones, ε-caprolactone and δ-valerolactone, were used as model monomers. Novozym 435 was shown to be highly reusable under the reaction conditions employed. Incomplete initiator conversion was observed during kinetics experiments, and computational docking studies were used to gain a deeper understanding of enzyme binding interactions during the reaction. Amphiphilic copolymers were prepared using free-radical copolymerisation with PEGMA, and produced materials were tested against three cell lines for cytotoxicity. To increase the greenness of the process, 2-methyl tetrahydrofuran was utilised as a biobased solvent throughout. In the following chapter, Chapter 3, biobased polyglycerol (PG) was explored as a building block to synthesise polyol polyesters for application as rheological modifiers. Polyglycerols underwent polycondensation with dimethyl succinate (DMS) in the presence of catalytic potassium carbonate to form hydrophilic polyesters. Of the polyglycerol lengths tested, PG4 was the most suitable due to its lower viscosity and lack of discolouration after reaction. The reaction achieved quantitative DMS conversion at mild temperatures (60-100 °C). Discolouration became more noticeable at elevated temperatures (140-180 °C). A selection of catalysts was screened, and K2CO3 was found to be the most suitable transesterification catalyst. Post-polymerisation functionalisation using succinic and maleic anhydrides was also explored. Increasing DMS loading resulted in cross-linked polymeric materials of varying swelling capability in aqueous media. This was highly promising for rheological modification of aqueous media. Evaluation of lightly cross-linked PG4-based polyesters as rheological modifiers for aqueous media was conducted in Chapter 4. PG4 polymerised with 1.25 equivalents of DMS yielded the highest performing viscosity enhancer, but it faced issues relating to rapid degradation in aqueous formulation. However, materials prepared with PG4 and 1.5 equivalents of DMS (PG4-1.5DMS) showed good rheological modification at loadings above 10 wt.% and exhibited greater stability in aqueous formulation. Increasing DMS loading beyond this point was detrimental to rheological modification performance. These formulations also displayed excellent electrolyte tolerance, maintaining thickening performance with minimal decrease in viscosity upon addition of NaCl or MgSO4. Good thickening performance was maintained in a pH range relevant for personal care applications. Oscillatory rheology showed the aqueous formulations exhibit viscoelasticity, with excellent structural recovery after multiple cycles of high shear strain. In addition, PG4-1.5DMS also exhibited significant water swellability, absorbing nearly 20 times its own mass of water. Degradation testing of aqueous formulations revealed PG4-1.5DMS undergoes hydrolysis, leading to acidification and reduced viscosity. To enhance PG4-1.5DMS performance, the gel fraction of the thickener was increased. This was achieved by freeze-drying following swelling in excess water. This process significantly improved rheological modification performance, achieving viscosity enhancements at a loading of only 2.5 wt.%. In aqueous formulation, the freeze-dried material maintained viscoelastic behaviour, exhibited excellent structural recovery, and demonstrated significantly increased swellability, absorbing nearly 50 times its own mass of water. Anionic polymerisation to synthesise linear polyglycerols of higher molar mass was investigated in Chapter 5. This was done to investigate the possibility of enhancing the rheological modifier by increasing the chain length of the hydrophilic segment. Anionic polymerisation of ethoxy ethyl glycidyl ether was employed for this purpose. Molar masses of up to 20.7 kg∙mol-1 were achieved. The reactions generally reached high conversions. To remove unreacted monomer, supercritical extraction with CO2 was employed as an environmentally friendly method. After extraction, linPG was obtained through deprotection using the heterogeneous acidic catalyst, Amberlyst 15. In Chapter 6, the same polyglycerols explored in Chapters 3 and 4 were investigated for their applicability as the basis of a photoactive resin for Additive Manufacturing. Volumetric printing has revolutionized Additive Manufacturing, offering an efficient approach whilst circumventing traditional layer-by-layer methodology. Polyglycerol-6 was acrylated using a scalable one-pot process. Successful volumetric printing of high-resolution models (smallest feature size 300 μm) was achieved, and reusability of the resin was demonstrated. Fluorescein was incorporated into the resin to show the ability to print objects embedded with a drug-like molecule. Micelles of 10,12-pentacosadiynoic acid were introduced to the resin and used to print thermoresponsive structures. This bio-based, biocompatible, scalable resin signifies a significant advancement towards environmentally sustainable resins in volumetric printing, fostering a more sustainable future with exciting applications.